2018
DOI: 10.1089/jmf.2017.0056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpha-Lipoic Acid on Clinical and Neurophysiologic Recovery of Carpal Tunnel Syndrome: A Double-Blind, Randomized Clinical Trial

Abstract: The objective of our study was to examine the effect of alpha-lipoic acid (ALA) on clinical and neurophysiologic outcomes after surgery for idiopathic carpal tunnel syndrome (CTS). We conducted a randomized, double-blind, placebo-controlled clinical trial in 20 adults diagnosed with idiopathic CTS after clinical and neurophysiologic assessment. Eligible participants took 600 mg ALA or placebo per day for 1 month before surgery, and for 2 months afterward. Further clinical and neurophysiologic assessments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
7
0
5
Order By: Relevance
“…Their results suggested a use of a conservative therapy based on neurotrophic agents, especially ALA, in order to control symptoms (both nocturnal and diurnal pain) and improve function 17 . Other studies demonstrated the efficacy of a combination of ALA and gamma-linolenic acid in up to severe CTS 16,18 . All the above mentioned studies [15][16][17][18] investigated specifically ALA use in CTS, but they did not distinguish between the ALA-R and racemic preparations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Their results suggested a use of a conservative therapy based on neurotrophic agents, especially ALA, in order to control symptoms (both nocturnal and diurnal pain) and improve function 17 . Other studies demonstrated the efficacy of a combination of ALA and gamma-linolenic acid in up to severe CTS 16,18 . All the above mentioned studies [15][16][17][18] investigated specifically ALA use in CTS, but they did not distinguish between the ALA-R and racemic preparations.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, another more recent prospective study had investigated the effect of ALA before and after surgery in CTS, they only assessed post-surgical improvement 18 . Luchetti et al reported short term results (two months followup) from an observational Italian multicentric study about conservative treatment of CTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Monroy et al used 600-mg ALA for 1 month before and for 2 months after CTS surgical treatment, leading to improve the clinical and neurophysiologic outcomes after surgery, so that in patients who received ALA in compared with placebo group, none of the participants had positive Phalen’s or Tinel’s signs at 12 weeks of follow-up; and based on electrophysiological findings, motor and sensory fiber latency and amplitude had significantly improved. 68 Presently, few studies have been conducted on the use of antioxidants for the improvement of peripheral nerve function in diabetic patients. More research in this field is hence warranted…”
Section: Development Of Medical Treatments In Diabetic Patients With ...mentioning
confidence: 99%
“…In particular, the regeneration index, which is defined as the total number of regenerated axons in the nerve segment distal to the ligation divided by the total number of regenerated axons in the nerve segment proximal to the ligation, was significantly higher in the group treated with enriched in ω-3 PUFAs diet than in non-treated animals. A double-blind randomised clinical trial on carpal tunnel patients has revealed that dietary supplementation of 600 mg/d of alpha-lipoic acid (ALA), an ω-3 PUFA, 1 month before and two months after surgery, significantly improved the neurophysiologic and clinical outcomes before and after surgery [52]. 100 mg/kg intraperitoneal ALA injection was done 24 and 1 h before crush injury…”
Section: Omega-3mentioning
confidence: 99%